Analisis Hubungan Stres Dengan Nyeri Kepala Primer Pada Mahasiswa Program Studi Kedokteran Fakultas Kedokteran Universitas Malahayati Tahun 2020 - Dharmawita Dharmawita; Dalfian Dalfian; Aprina Dwi Lestari (Universitas Malahayati, 2021)
ABSTRACT: ANALYSIS OF THE RELATION OF STRESS WITH PRIMARY HEAD PAIN IN STUDENTS OF MEDICAL STUDY PROGRAM FACULTY OF MEDICINE MALAHAYATI UNIVERSITY Background: According to the World Health Organization, in 2012, it was stated that primary headaches showed a very high prevalence rate. Globally, it is estimated that the prevalence of headaches in adults reaches 50%. Where it was reported in the last year that adults aged 18-65 years in the world suffered from headaches, and among this population, 30% had migraines, while more than 70% of the population reported suffering from TTH. Objective: This study aims to determine the relationship between stress and primary headache. Method: This study used an observational analytic method with a cross-sectional approach. With the sample population used by students of the 2017 Malahayati University medical faculty medical study program. Result: The results of this study showed that 180 respondents experienced mild stress levels of 2 people (1.1%), moderate stress 124 people (68.9%), and 54 people experiencing severe stress (30%). There were 114 respondents (63.3%) who experienced primary headaches (migraines) and 66 respondents (36.7%) experienced tension-type headaches (TTH). From the results of the bivariate analysis of the study using the chi-square method, it was found that the p-value was 0.000 (p <0.05). Conclusion: There is a relationship between stress levels and primary headaches in students of the medical study program at the medical faculty of Malahayati University in 2020 with p = 0.000 (<0.05), OR CI value = 3.841. Keywords: Stress, Migraine, Tension-type headache, Cluster headache INTISARI: ANALISIS HUBUNGAN STRES DENGAN NYERI KEPALA PRIMER PADA MAHASISWA PROGRAM STUDI KEDOKTERAN FAKULTAS KEDOKTERAN UNIVERSITAS MALAHAYATI Latar Belakang : Menurut World Health Organization pada tahun 2012 menyatakan bahwa nyeri kepala jenis primary headache menunjukkan angka prevalensi yang sangat tinggi. Secara global, diperkirakan prevalensi nyeri kepala pada orang dewasa mencapai angka 50%. Dimana dilaporkan dalam satu tahun terakhir orang dewasa berumur 18-65 tahun di dunia menderita nyeri kepala, dan diantara populasi tersebut 30% nya menderita migrain, sedangkan lebih dari 70% populasi melaporkan menderita TTH.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan antara stres dengan nyeri kepala primer.Metode: Penelitian ini menggunakan metode Analitik observasional dengan pendekatan cross sectional. Dengan populasi sampel yang digunakan mahasiswa program studi kedokteran fakultas kedokteran Universitas Malahayati angkatan 2017.Hasil penelitian : Hasil dari penelitian ini 180 responden didapatkan bahwa responden yang mengalami tingkatan stres ringan 2 orang (1,1%), stres sedang 124 orang (68,9%) dan yang mengalami stres berat 54 orang (30%). Responden yang mengalami nyeri kepala primer yaitu migrain sebanyak 114 orang (63,3%) dan yang mengalami nyeri kepala tipe tegang (TTH) sebanyak 66 orang (36,7%). Dari hasil analisis bivariat penelitian dengan metode chi square dimana didapati nilai p-value sebesar 0,000 (p < 0,05).Kesimpulan : Terdapat hubungan anatara tingkat stres dengan nyeri kepala primer pada mahasiswa program studi kedokteran fakultas kedokteran Universitas Malahayati Tahun 2020 dengan p = 0,000 (<0,05), nilai OR CI = 3,841. Kata Kunci: Stress, Migrain, Tension-type headache, Cluster headache.